REGULATORY AUTOPHOSPHORYLATION SITES ON PROTEIN KINASE C-δ AT Thr(141) AND Thr(295) - Rybin, Vitalyi O. (2009)
Protein kinase C-δ (PKCδ) is a Ser/Thr kinase that regulates a wide range of cellular responses. This study identifies novel in vitro PKCδ autophosphorylation sites at Thr(141) adjacent to the pseudosubstrate domain, Thr(218) in the C1A–C1B interdomain, Ser(295), Ser(302), and Ser(304) in the hinge region, and Ser(503) adjacent to Thr(505) in the activation loop. Cell-based studies show that Thr(141) and Thr(295) also are phosphorylated in vivo and that Thr(141) phosphorylation regulates the kinetics of PKCδ downregulation in COS7 cells. In vitro studies implicate Thr(141) and Thr(295) autophosphorylation as modifications that regulate PKCδ activity. A T141D substitution markedly increases basal lipid-independent PKCδ activity; the PKCδ-T141D mutant is only slightly further stimulated in vitro by PMA treatment, suggesting that Thr(141) phosphorylation relieves autoinhibitory constraints that limit PKCδ activity. Mutagenesis studies also indicate that a phosphorylation at Thr(295) contributes to the control of PKCδ substrate specificity. We previously demonstrated that PKCδ phosphorylates the myofilament protein cardiac troponin I (cTnI) at Ser(23)/Ser(24) when it is allosterically activated by lipid cofactors and that the Thr(505)/Tyr(311)-phosphorylated form of PKCδ (that is present in assays with Src) acquires as additional activity toward cTnI-Thr(144). Studies reported herein show that a T505A substitution reduces PKCδ-Thr(295) autophosphorylation and that a T295A substitution leads to a defect in Src-dependent PKCδ-Tyr(311) phosphorylation and PKCδ-dependent cTnI-Thr(144) phosphorylation. These results implicate PKCδ-Thr(295) autophosphorylation as a lipid-dependent modification that links PKCδ-Thr(505) phosphorylation to Src-dependent regulation of PKCδ catalytic function. Collectively, these studies identify novel regulatory autophosphorylations on PKCδ that serve as markers and regulators of PKCδ activity.